1993
DOI: 10.1115/1.2910689
|View full text |Cite
|
Sign up to set email alerts
|

Natural Convective Heat Transfer in a Divided Vertical Channel: Part I—Numerical Study

Abstract: This is a two-part study of two-dimensional laminar natural convection heat transfer in a divided vertical channel. The divided channel consists of an isothermal dividing plate located on the center line of a vertical channel formed by two isothermal walls. The study examines the effect of Rayleigh number, plate-to-channel length ratio, vertical plate position, and plate thickness on the heat transfer rate from the channel walls, the dividing plate, and the channel as a whole. In Part I, solutions to both the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…, and thickness t are inserted between the long plates. A related geometry has been studied numerically in [9]. The flow through the plates is laminar forced convection driven by the imposed pressure difference P .…”
Section: Modelmentioning
confidence: 99%
“…, and thickness t are inserted between the long plates. A related geometry has been studied numerically in [9]. The flow through the plates is laminar forced convection driven by the imposed pressure difference P .…”
Section: Modelmentioning
confidence: 99%
“…These two limits were referred as the fully developed limit and single plate limit. Moreover, in Naylor and Tarasuk (1993a), these two limits have been established for the vertical plate inside a channel and referred as the fully developed limit and isolated plate limit. In the present configurations the two limits may also be referred to the fully developed limit and unconfined cylinder limit.…”
Section: Central Lateral Position Inside the Channelmentioning
confidence: 99%
“…[29]. The numerical study [28] showed that the heat transfer rate from the auxiliary plate can be significantly enhanced by the presence of the channel walls. The highest average Nusselt number for complete system (channel and plate as a whole) was obtained by positioning the plate at the bottom of the channel.…”
Section: Introductionmentioning
confidence: 97%
“…An analysis of the configuration with the channel walls and the auxiliary plate at uniform temperature was carried out numerically in Ref. [28] and experimentally in Ref. [29].…”
Section: Introductionmentioning
confidence: 99%